Conserved V‐ATPase c subunit plays a role in plant growth by influencing V‐ATPase‐dependent endosomal trafficking. Issue 1 (28th April 2015) - Zhou, Aimin; Bu, Yuanyuan; Takano, Tetsuo; Zhang, Xinxin; Liu, Shenkui
Summary: In plant cells, the vacuolar‐type H + ‐ATPases (V‐ATPase) are localized in the tonoplast, Golgi, trans ‐Golgi network and endosome. However, little is known about how V‐ATPase influences plant growth, particularly with regard to the V‐ATPase c subunit (VHA‐c). Here, we characterized the function of a VHA‐c gene from Puccinellia tenuiflora (PutVHA‐c) in plant growth. Compared to the wild‐type, transgenic plants overexpressing PutVHA‐c in Arabidopsis thaliana exhibit better growth phenotypes in root length, fresh weight, plant height and silique number under the normal and salt stress conditions due to noticeably higher V‐ATPase activity. Consistently, the Arabidopsis atvha‐c5 mutant shows reduced V‐ATPase activity and retarded plant growth. Furthermore, confocal and immunogold electron microscopy assays demonstrate that PutVHA‐c is mainly localized to endosomal compartments. The treatment of concanamycin A (ConcA), a specific inhibitor of V‐ATPases, leads to obvious aggregation of the endosomal compartments labelled with PutVHA‐c‐GFP. Moreover, ConcA treatment results in the abnormal localization of two plasma membrane (PM) marker proteins Pinformed 1 (AtPIN1) and regulator of G protein signalling‐1 (AtRGS1). These findings suggest that the decrease in V‐ATPase activity blocks endosomal trafficking. Taken together, our results strongly suggest that the PutVHA‐c plays an important role in plant growth by influencing V‐ATPase‐dependent endosomal trafficking.